2010
DOI: 10.1021/jp107783z
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Stabilized Criegee Intermediates from Ozonolysis of Limonene with Sulfur Dioxide: Ab Initio and DFT Study

Abstract: The mechanism of the reaction of the sulfur dioxide (SO(2)) with four stabilized Criegee intermediates (stabCI-CH(3)-OO, stabCI-OO, stabCIx-OO, and stabCH(2)OO) produced via the ozonolysis of limonene have been investigated using ab initio and DFT (density functional theory) methods. It has been shown that the intermediate adduct formed by the initiation of these reactions may be followed by two different reaction pathways such as H migration reaction to form carboxylic acids and rearrangement of oxygen to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 83 publications
6
45
1
Order By: Relevance
“…20,23 , as well as laboratory experiments 24 , have found the SO 2 1 sCI reaction to be significantly faster than previously thought. Another property that influences the oxidation capacity of sCIs is their lifetime against unimolecular decomposition reactions.…”
Section: Research Lettermentioning
confidence: 77%
“…20,23 , as well as laboratory experiments 24 , have found the SO 2 1 sCI reaction to be significantly faster than previously thought. Another property that influences the oxidation capacity of sCIs is their lifetime against unimolecular decomposition reactions.…”
Section: Research Lettermentioning
confidence: 77%
“…Some of these studies focused in particular on the possible impact that SCIs might have on the formation of sulfuric acid (H 2 SO 4 ) in the gas phase, following Mauldin III et al (2012), who suggested that Criegee intermediates are the missing SO 2 oxidant needed to close the sulfuric acid budget over a boreal forest. This is supported by theoretical and laboratory studies that have determined a rate coefficient between SCIs and sulfur dioxide (SO 2 ) of the order of 10 −11 cm 3 molecule −1 s −1 (Aplincourt and Ruiz-López, 2000;Jiang et al, 2010;Kurteìn et al, 2011;Vereecken et al, 2012;Welz et al, 2012;Liu et al, 2014b;Sheps et al, 2014;Stone et al, 2014). As the main atmospherically relevant oxidiser of SO 2 in the gas phase is the OH radical with a rather slow rate coefficient at ambient temperature and pressure of 2 × 10 −12 cm 3 molecule −1 s −1 (Atkinson et al, 2004), the high rate coefficient for SO 2 oxidation would allow SCIs to have a significant impact on the H 2 SO 4 formation even if present in small concentrations.…”
mentioning
confidence: 78%
“…Previous theoretical studies have shown that the first step of the sCI with SO 2 is the formation of a cyclic secondary ozonide (SOZ) that can undergo decomposition to the corresponding carbonyl and SO 3 or isomerisation involving a 1,2-H-shift leading to an organic acid and SO 2 (Jiang et al, 2010;Kurten et al, 2011). The release of SO 3 would produce H 2 SO 4 in the presence of water molecules.…”
Section: Theoretical Insightsmentioning
confidence: 99%